Migrant workers, migrants, internally displaced persons, asylum seekers and refugees - The silent sufferers of the COVID-19 pandemic: A brief review of media reports - Syed, Nabeel Kashan; Al-kasim, Mohamed Ahmed; Alqahtani, Saad; Meraya, Abdulkarim M.; Syed, Mamoon H.; Elnaem, Mohamed Hassan Abdelaziz; Griffiths, Mark (CDS Press, 2022)
Like other vulnerable groups, the pandemic has severely and negatively impacted marginalized groups, including migrant laborers, documented and undocumented migrants, internally displaced persons (IDPs), refugees, and asylum seekers. The present study briefly reviewed cases of attempted and completed suicide while also examining their causality among national and international migrant workers, migrants, IDPs, refugees, and asylum seekers during the ongoing pandemic. This study utilized retrospective extraction of suicide-related information from earlier published press reports. With regards to COVID-19- related suicides, this method has had widespread acceptability and has previously been extensively used in countries of South-East Asia for reporting suicides in academic journals. The authors located 26 relatively complete details of migrant worker suicides and suicide attempts from India and Singapore and 46 cases of migrant suicides from Malaysia with partially complete details. Lockdown-related health, job, and financial uncertainties coupled with pandemic-related emotional as well as mental stressors were some of the reported reasons for the alleged suicides and suicide attempts. Considering the psychological impact of the COVID-19 pandemic, the role of mental health services becomes increasingly important. Governments should take the lead in safeguarding the financial, physical, and mental well-being of all its citizens with special emphasis on the most vulnerable populations and high-risk groups for the entire period of the pandemic, to avert any unneeded loss of life related to suicides.